KEPUASAN MASYARAKAT TERHADAP KUALITAS PELAYANAN KANTOR PERTANAHAN KABUPATEN INDRAMAYU - Riyadi, Slamet; Hermawan, Aji; Sumarwan, Ujang (Jurnal Ilmu Keluarga dan Konsumen, 2015)
Customer satisfaction research is not only carried out by the business sector but also carried out by the government in the framework of public service. Satisfaction of the people in this study was measured by five dimensions that were reliability, responsiveness, assurance, empathy, and tangible. This study aimed to examine the level of public satisfaction to service quality of Land Agency of Indramayu District and the dimensions of the of the satisfaction that mostly influence, which will be used as the basis for determining policy. The results obtained that the level of public satisfaction to service quality as a whole was in quite satisfied. This was indicated by the value of the average society response of 2,85 (from maximum score of 4). Meanwhile, the dimensions of people's satisfaction that mostly influence were empathy and tangible. The amount of dimensions of empathy and tangible contribution to the satisfaction was indicated by the value of the loading factor; each dimension had a value of0,61 and 0,41 with the positive direction. It means that increasing quality of service especially in empathy and tangible dimensions will increase the public satisfaction. Several policies from these results could be taken by the Land Agency of Indramayu District, such as creating an integrated communication system, increasing the number of employees on counters, and training for employees.